Navigating Through Multiple Languages: A Study of Multilingual Students’ Use of their Language Repertoire Within a French Canadian Minority Education Context - Sweeney, Shannon D. (Université d'Ottawa / University of Ottawa, 2013)
The presence of Allophone students in French-language secondary schools in Ottawa is gradually increasing. While the politique d’aménagement linguistique (PAL) insists on the use of French within the school, one may begin to wonder which language Allophone students are speaking. French? English? Their native language(s)? This qualitative case study of four multilingual Allophone students explores their language repertoire use in relation to their desired linguistic representation, their linguistic proficiency in French, English, and their native language(s), and their perceptions of language prestige. The results indicate that students spoke a significant amount of English, some French (particularly with their teacher or Francophone classmates), and minimal amounts of their native language. Recommendations are suggested to increase the effectiveness of PAL within a Francophone minority context and to ensure that the policy’s objects are attained.
Keywords: Linguistic Repertoire; Language Use; Minority Context; Language Policy; Multilingualism